Observation of Gravitational Waves from a Binary Black Hole Merger - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Abernathy, M. R.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, P.; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; et al. (Amer Physical Soc, 2016)
On September 14, 2015 at 09: 50: 45 UTC the two detectors of the Laser Interferometer Gravitational-Wave Observatory simultaneously observed a transient gravitational-wave signal. The signal sweeps upwards in frequency from 35 to 250 Hz with a peak gravitational-wave strain of 1.0 x 10(-21). It matches the waveform predicted by general relativity for the inspiral and merger of a pair of black holes and the ringdown of the resulting single black hole. The signal was observed with a matched-filter signal-to-noise ratio of 24 and a false alarm rate estimated to be less than 1 event per 203 000 years, equivalent to a significance greater than 5.1 sigma. The source lies at a luminosity distance of 410(-180)(+160) Mpc corresponding to a redshift z = 0.09(-0.01)(+0.03). In the source frame, the initial black hole masses are 36(-4)(+5)M(circle dot) and 29(-4)(+4)M(circle dot), and the final black hole mass is 62(-4)(+4) M-circle dot, with 3.0(-0.5)(+0.5) M(circle dot)c(2) radiated in gravitational waves. All uncertainties define 90% credible intervals. These observations demonstrate the existence of binary stellar-mass black hole systems. This is the first direct detection of gravitational waves and the first observation of a binary black hole merger.